Biotechnological revalorization of Tequila waste and by-product streams for cleaner production – A review from bio-refinery perspective. (20th January 2018) - Alemán-Nava, Gibrán S.; Gatti, Ilaria Alessandra; Parra-Saldivar, Roberto; Dallemand, Jean-Francois; Rittmann, Bruce E.; Iqbal, Hafiz M.N.
Abstract: In this paper, industrial processing and biotechnological revalorization of Tequila waste and by-product streams have been reviewed. Tequila production process generates different kind of waste and by-products with a huge potential to produce value-added products. Therefore, many research projects, scientific investigations and innovative utilizations of such waste and by-product streams have been the object of recent studies. Moreover, the bio-based transformation from a petrochemical-based economy to a bio-based economy necessitates the novel exploitation of cost-effective natural materials for both future biorefinery development and a range of value-added products of interests. The present review article focuses on an area not comprehensively reviewed previously, the potential of utilizing waste and by-product streams from current Tequila industry activities. The first part of this review focused on various processing aspects and prospects on the fermentative production of Tequila. In the second and third parts, statistical and sustainable aspects and the generation of waste and by-product streams of Tequila industry are critically reviewed, respectively. In the fourth part, various industrial and biotechnological applications of Tequila's wastes are comprehensively discussed from a bio-refinery perspective. In conclusion, it is evident that biotransformation of waste and by-product streams has great potential and significant prospects for wider industrial and biotechnological applications.